PELATIHAN PENULISAN KARYA ILMIAH UNTUK MENINGKATKAN KOMPETENSI PROFESIONAL GURU DI SMP N 2 JATEN KARANGANYAR - Octaviani, Andri; Suseno, Adnan Terry (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
The purpose of this service is to find a solution to the problem of teachers' lack of knowledge in writing scientific papers in the form of class action research. The method of PkM activities in the form of socialisation and mentoring In addition, in this activity, to find out the experience of writing scientific papers carried out by teachers, the team also distributed a questionnaire containing several questions. Based on the data obtained from the questionnaire distribution, only about 10% of teachers in the school have written scientific papers and some have been published in a journal, the rest, the experience of writing scientific papers of teachers is still limited to theses and papers. One of the factors causing the low number of scientific papers published in journals is because teachers do not understand the steps of writing scientific papers. From the results of the mentoring, the teachers' skills to write rich scientific papers increased. The scientific paper training discussed the urgency of writing, the systematics of making papers, and the systematics of making research reports. The material was delivered by lecturers The results of the class action research will be finalised.